Pengaruh Viral Marketing terhadap Purchase Intention dan Keputusan Pembelian - Aminudin Azis; Ina Syarifah (LITERATUS, 2022)
Marketing a product and/or service requires a strategy to be able to competen. Viral marketing is one of the leading strategies in the current era of technological advancement. Viral Marketing Strategy is able to introduce products and/or services to everyone without being limited by distance. Social media can be used as a means of implementing a Viral Marketing strategy. The aim of this paper to find out the effect of viral marketing on purchase intention and buying decision, effect of purchase intention on buying decision. This research is an explanatoru research. The sample includes 200 respondens from the number of indicators multiplied by 5. This study was a quantitative approarch and daya were analyzed using Partial Least Square with software SmartPLS. The results showed a positif and significant effect of purchase intention and buying dicision and purchase dicision positif and significant effect of buying decision.